(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
This study was conducted to assess the health risk of heavy metals from some fruits and vegetables sold in the Dutse Ultra-modern market, Jigawa State. Two fruits (watermelon and orange) and two vegetables (okra and spinach) were selected randomly from two vendors for two consecutive periods within one week. The samples were transported to the laboratory for acid digestion. Atomic Absorption Spectrophotometer (AAS) was used for the determination of heavy metal (Cd, Pb, Zn, Fe, Mg, Cr and Ni) concentration in the various samples. Bioaccumulation factor, pollution index, hazard quotient and hazard index were calculated and compared with WHO standard. Results obtained in the present study revealed that Cd levels in the samples were significantly higher as compared with the control value (0.2 mg/mL). Pb, Fe, Cr and Ni evaluated were insignificant as compared with their control (2 mg/mL, 1 mg/mL, 1.3 mg/mL and 10 mg/mL, respectively). The results revealed only Cr (1.5) and Ni (1.7) have significantly high bioaccumulation factors while all other heavy metals show relatively low bioaccumulation. The pollution index of heavy metals in the samples of fruits and vegetables evaluated shows a relatively low pollution index, values obtained vary from 0.11 in Pb to 0.9 in Ni. While hazard quotients and hazard index were insignificant. The study concludes that okra, spinach, orange and watermelon in the Dutse ultra-modern market in Jigawa state despite their proximity to the mechanic village and a lot of activities occurring may not cause a serious health threat to human consumption. The study recommends further studies on other fruits and vegetables not selected for this study.